Distribuição dos lotes de cargas procurando maximizar o carregamento em semi-reboques do tipo baú sem causar excesso de peso - Souza, Cezar Augusto Matos e (2007)
The traffic of vehicles used into the highway transportation of cargoes with overweight at this country, that's a recurrent problem of extreme gravity, in as much as this excess , acts reducing the service period that highways. The crescent competitive sector of the products distribution completed the organizations to improve their procedures , creating the method of loads transfer, but the utilization of this method is demaged due to the overweight into the tract unit rear axle, even when the semi-plaster is loaded with values of weight far below of the permitted on law. We can stress this shipment made with values beyond from the foreseen on law bring many problems on the operation of cargoes transportation, as the overweight fine and the requirement of the loads excess to be transhipped to another vehicle, generates delays and increasing the costs of the whole process, acting on the company competitiveness, injuring the pavement. Then, the objective of this work is offer a solution that could be technique and, at the same time, a low cost investment, to the sector companies, mainly, for the ones that uses sets of two axles unit tract and semi - plaster of triple tandem axle. Providing the results of a cargo into the rear axle tract unit and of the triple tandem axle, through the calculations of static balance considering the stowage factor and the weight force application point from of each lot of loads in relation to the tract unit rear axle. In this way, it offered a necessary ambiance for the case study, the company increases the average weight loaded for semi-plaster in 22,95%, without overweight.